PROBLEMS IN EDUCATIONAL PRACTICE AND THE THEORY OF TEACHING ZOOLOGICAL SCIENCES (Conferencea, 2022)
The relevance of this article is due to the problems in educational practice and the theory of teaching Zoological sciences. The effectiveness of teaching zoology and the history of teaching and learning zoology science has been discussed. The opinions and ideas of famous zoologists have been analyzed and discussed.